Corporate Governance and Earnings Management Before Share Repurchase Announcements in Singapore - CHUA, Jian Ming (Institutional Knowledge at Singapore Management University, 2010)
Share repurchase in Singapore was legalized in 1998. It is well known that investors view share repurchase as good news. This study is based on share repurchase announcements from 2006 to 2009. The mean Cumulative Market-Adjusted Returns (CAR) for the period [0, +1] and [-1, +1] are significant at 1.25% and 1.33% respectively. In Singapore, there are positive abnormal returns following share repurchase announcements in support of the ―free cash flow‖ hypothesis. By using the Singapore Corporate Governance Index as a proxy, the weakly governed companies exhibit the strongest, positive and significant CAR of 2.62% for the period [0, +1]. Lastly, one year prior to share repurchase announcements; companies on average manage their discretionary current accrual downwards by 1.44%. The companies with the best corporate governance manage their earnings downwards by 2.69%. In a regression, the CAR for the period [0, +1] changes by 0.1097% when the discretionary current accrual changes by 1%.